2014
DOI: 10.1007/s00198-014-2707-4
|View full text |Cite
|
Sign up to set email alerts
|

High fluoride and low calcium levels in drinking water is associated with low bone mass, reduced bone quality and fragility fractures in sheep

Abstract: SummaryChronic environmental fluoride exposure under calcium stress causes fragility fractures due to osteoporosis and bone quality deterioration, at least in sheep. Proof of skeletal fluorosis, presenting without increased bone density, calls for a review of fracture incidence in areas with fluoridated groundwater, including an analysis of patients with low bone mass.IntroductionUnderstanding the skeletal effects of environmental fluoride exposure especially under calcium stress remains an unmet need of criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 43 publications
(41 reference statements)
2
23
0
1
Order By: Relevance
“…The deteriorated mechanical properties with aging and osteoporosis are in agreement with previous studies . Regarding the mechanical properties after fluoride treatment, in vitro studies have shown that the exposure of bone specimen to fluoride causes a reduction in bone strength, while in vivo animal studies have shown positive as well as negative effects of fluoride on biomechanical properties . For treatment with strontium, there is still disagreement as to whether the biomechanical properties of bone are altered by the incorporation of strontium into the bone mineral matrix.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The deteriorated mechanical properties with aging and osteoporosis are in agreement with previous studies . Regarding the mechanical properties after fluoride treatment, in vitro studies have shown that the exposure of bone specimen to fluoride causes a reduction in bone strength, while in vivo animal studies have shown positive as well as negative effects of fluoride on biomechanical properties . For treatment with strontium, there is still disagreement as to whether the biomechanical properties of bone are altered by the incorporation of strontium into the bone mineral matrix.…”
Section: Discussionsupporting
confidence: 88%
“…Here, the F and SR treatment groups had significantly higher backscattered signal intensities in comparison to non‐treated osteoporotic bone resulting in a 7% increase in Ca mean and 5% increase in Ca peak, although these values were still lower than in the control group. Indeed, treatment of osteoporosis with fluoride is associated with a higher mineralization pattern and may even lead to fluorosis at high fluoride doses with an abnormal bone mineralization and enlarged mineral crystals . However, the results show that treatment with fluoride at a dose of < 20 mg/d partly antagonizes the decreased mineral content due to osteoporosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We speculate that this lack of mineralization makes this bone segment more prone to mechanical stress, which may result in subchondral insufficiency fractures. ** References 2,4,16,32,34,43,45,50,52. Vol. 43, No.…”
Section: Resultsmentioning
confidence: 99%
“…The GLP-2R is expressed on osteoclasts, and its activation is believed to reduce catabolic activity of these cells [86]. Therefore, GLP-2 therapy may be useful in livestock production to improve bone health and prevent conditions such as osteopenic disease in swine or fluorosis, which is most common among cattle, horses, and sheep in fluoride-contaminated environments [107] and increases the incidence of bone fractures in sheep [108]. Benefits of GLP-2 for these conditions include both improved calcium uptake through its effects on increasing calcium transporter expression in the intestinal tract and its direct effects on reducing bone resorption.…”
Section: Potential Uses Of Glp-2 and Stimulators Of Glp-2 Secretion Imentioning
confidence: 98%